Information technologiesin the national security system of the country: development problems - Kramskoy, D. Yu.; Poberezhny, D. O.; Pererva, P. G. (My University, 2023)
It has been proven that the information security of the state is determined by the degree of its protection and the stability of the main spheres of life in relation to dangerous, destabilizing, destructive informational influences affecting the interests of the country at the level of both introduction and extraction of information.
Інформаційні технології в системі національної безпеки країни: проблеми розвитку
Keywords: іnformation security; state; identification methods; support measures